Genetic manipulation of trehalose‐6‐phosphate synthase results in changes in the soluble sugar profile in transgenic sugarcane stems. (7th November 2021) - Gabriel, Casey; Fernhout, Jean‐Jacque; Fichtner, Franziska; Feil, Regina; Lunn, John E.; Kossmann, Jens; Lloyd, James R.; van der Vyver, Christell
Abstract: Trehalose is a non‐reducing disaccharide widely distributed in nature. The trehalose biosynthetic intermediate, trehalose 6‐phosphate (Tre6P) is an essential regulatory and signaling molecule involved in both regulation of carbon metabolism and photosynthesis. To investigate the effect of altered trehalose synthesis on sucrose accumulation in sugarcane ( Saccharum spp . hybrid), we independently overexpressed the Escherichia coli otsA (trehalose‐6‐phosphate synthase; TPS) and otsB (trehalose‐6‐phosphate phosphatase; TPP) genes and additionally partially silenced native TPS expression. In mature cane, sucrose levels in the otsA transgenic plants were lowered, whereas sucrose levels in the otsB transgenic plants were increased. Partial silencing of TPS expression in sugarcane transformed with a TPS‐targeted microRNA recombinant construct was confirmed in leaf and mature internode tissue of transgenic plants. Most of the silencing transgenic lines accumulated trehalose at lower levels than the wild‐type (WT) plants. The immature stalk tissue of these transgenic lines had lower levels of glucose and fructose, whereas the mature internode tissue had lower sucrose and glucose levels, when compared with the WT. Furthermore, various minor metabolites and sugars were detected in the sugarcane plants, which mostly decreased as the stalk tissue of the cane matured. The results demonstrate that manipulation of Tre6P/trehalose metabolism has the potential to modify the profile of soluble sugars accumulated in sugarcane stems.